Histamine and Scombrotoxins - Hungerford, James M. (Toxicon (Oxford), 2021)
Histamine intoxications result when histamine-metabolizing enzymes are compromised or overwhelmed by dietary histamine in the human body. This can occur either due to metabolic enzyme deficiencies, such as in histamine intolerance to wines, aged cheese and other foods or from high concentrations of histamine following ingestion of decomposed fish. The presence of histamine in decomposed fish and fish products results from bacterial decarboxylation of free L-histidine following product mishandling. Consequently, histamine intoxications from mishandled fish, commonly referred to as scombrotoxin fish poisoning (SFP) or scombroid poisoning, require high levels of free L-histidine only found in certain species of pelagic fish. Differential diagnosis is required of clinicians since dietary histamine intoxications produce the same symptoms typical of release of endogenous histamine due to IgE -mediated seafood allergies or anisakiasis. Although high levels of dietary histamine are responsible for SFP, histamine has important physiological functions and tends to exert toxic effects only at doses beyond the physiological range. Endogenous histamine is essential to local immune responses, regulation of gastric acid secretion in the gut, and neurotransmission in the central nervous system. Scombrotoxins, postulated to explain histamine's augmented toxicity in scombrotoxic fish, are a milieu of histamine and other bioactives. Since time-and-temperature abuse is required to produce high levels of histamine in fish, management consists of ensuring proper handling by identifying hazards and critical control points (HACCP) and maintaining a “cold chain” from catch to consumption. Reference methods for detecting histamine have received increased attention and the European Commission has validated a popular precolumn dansylation-based HPLC method through inter-laboratory collaboration and studied method equivalence with the AOAC fluorescence method 977.13 recognized by Codex Alimentarius. Much progress has been made during the last decade in the development and validation of rapid screening methods for detecting histamine in food and especially in fish products. These include many innovative sensors and several validated commercial test kits, many of them based on a recombinant form of the enzyme histamine dehydrogenase (HD). •Scombrotoxin fish poisoning is also known as scombroid poisoning and histamine fish poisoning.•Scombrotoxin fish poisoning is a common cause of food poisoning worldwide.•Dietary histamine in decomposed fish is formed by bacterial enzymes and is due to mishandling.•Scombrotoxins are bioactives postulated to augment the toxicity of dietary histamine.•Many new rapid screening methods for histamine detection have been developed and validated.